2016
DOI: 10.5194/isprsannals-iii-5-159-2016
|View full text |Cite
|
Sign up to set email alerts
|

Panorama Image Sets for Terrestrial Photogrammetric Surveys

Abstract: ABSTRACT:High resolution 3D models produced from photographs acquired with consumer-grade cameras are becoming increasingly common in the fields of geosciences. However, the quality of an image-based 3D model depends on the planning of the photogrammetric surveys. This means that the geometric configuration of the multi-view camera network and the control data have to be designed in accordance with the required accuracy, resolution and completeness. From a practical application point of view, a proper planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several studies have achieved dense reconstruction using panoramic imaging models or panoramic data (Barazzetti et al, 2010;Wahbeh et al, 2016;Zhu et al, 2020). Piermattei et al (2016) conducted a study in which they simulated the panoramic mode by rotating the camera to capture multiview images of the same site. The results of the photogrammetric processing showed that the panoramic images had a more complete and detailed modelling effect than single views.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have achieved dense reconstruction using panoramic imaging models or panoramic data (Barazzetti et al, 2010;Wahbeh et al, 2016;Zhu et al, 2020). Piermattei et al (2016) conducted a study in which they simulated the panoramic mode by rotating the camera to capture multiview images of the same site. The results of the photogrammetric processing showed that the panoramic images had a more complete and detailed modelling effect than single views.…”
Section: Introductionmentioning
confidence: 99%
“…Piermattei et al. (2016) conducted a study in which they simulated the panoramic mode by rotating the camera to capture multiview images of the same site. The results of the photogrammetric processing showed that the panoramic images had a more complete and detailed modelling effect than single views.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, terrestrial and aerial SfM surveys can be combined to overcome the main limits of both techniques [34]. In fact, the terrestrial approach can provide an accurate representation of complex surfaces [35] but its use is limited to small areas and it may poorly represent a homogeneous terrain. On the contrary, aerial surveys (e.g., using Unmanned Aerial Veicles-UAV) can cover wide areas quickly [36], but aerial-derived DEMs are not optimal in cases of steep or vertical terrains [37].…”
Section: Introductionmentioning
confidence: 99%